2020
DOI: 10.3390/plants9070805
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Fruit Callus Culture as a Model System to Study Color Development and Cell Wall Remodeling during Strawberry Fruit Ripening

Abstract: Cell cultures derived from strawberry fruit at different developmental stages have been obtained to evaluate their potential use to study different aspects of strawberry ripening. Callus from leaf and cortical tissue of unripe-green, white, and mature-red strawberry fruits were induced in a medium supplemented with 11.3 µM 2,4-dichlorophenoxyacetic acid (2,4-D) under darkness. The transfer of the established callus from darkness to light induced the production of anthocyanin. The replacement of 2,4-D by abscis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Plant cell culture is a convenient system to study metabolite biosynthesis, cell development, and response to specific stimuli, as it allows for more precise control of treatment conditions ( Onofrio et al., 2009 ; Almagro et al., 2014 ; Ayenew et al., 2015 ; Ric-Varas et al., 2020 ). Previous studies have shown that sugar, light, heat, and jasmonate can induce the biosynthesis of anthocyanins or PAs in grape cell cultures ( Larronde et al., 1998 ; Vitrac et al., 2000 ; Decendit et al., 2002 ; Zhang et al., 2002 ; Onofrio et al., 2009 ; Ayenew et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant cell culture is a convenient system to study metabolite biosynthesis, cell development, and response to specific stimuli, as it allows for more precise control of treatment conditions ( Onofrio et al., 2009 ; Almagro et al., 2014 ; Ayenew et al., 2015 ; Ric-Varas et al., 2020 ). Previous studies have shown that sugar, light, heat, and jasmonate can induce the biosynthesis of anthocyanins or PAs in grape cell cultures ( Larronde et al., 1998 ; Vitrac et al., 2000 ; Decendit et al., 2002 ; Zhang et al., 2002 ; Onofrio et al., 2009 ; Ayenew et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, our effort was focused on design and preparation of CNC-AN lipstick sunscreens that were safe and simple for human lip photoprotection. Inspired by natural fibers of textile products, cellulose from hemp stalk enveloped with AN UV absorbers in the vacuoles was developed using bionic design [17]. Binding of anthocyanins to acid hydrolysis of cellulose, the lipstick exhibited pleasing texture due to the reddish color.…”
Section: Introductionmentioning
confidence: 99%